1999
DOI: 10.1109/20.800620
|View full text |Cite
|
Sign up to set email alerts
|

Metal-bonded Co-ferrite composites for magnetostrictive torque sensor applications

Abstract: A new class of magnetomechanical sensor materials, Co-ferrite (Co0.Fe203) and metal-bonded (Ag, Ni, CO) Co-ferrite composites, has been investigated. These materials exhibited magnetostriction in excess of 200 ppm and high d3, (aUiJH), coefficient, 1.3~10' A'm, at low applied field ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 9 publications
3
54
1
Order By: Relevance
“…13 Our experimental results confirmed that the metal-bonded Co-ferrite composite exhibits the same behavior. This effect, which is due to the magnetic moments on different lattice sites changing differently with temperature, also caused part of the decrease with increasing temperature of the remanent magnetization of the ring-shaped ferrite composite.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…13 Our experimental results confirmed that the metal-bonded Co-ferrite composite exhibits the same behavior. This effect, which is due to the magnetic moments on different lattice sites changing differently with temperature, also caused part of the decrease with increasing temperature of the remanent magnetization of the ring-shaped ferrite composite.…”
Section: Discussionsupporting
confidence: 78%
“…16,19,21 Due to the fact that the magnetizations of the sublattices of ferrites have opposite signs and different temperature dependence, the temperature dependence of the magnetic properties of ferrites, such as saturation magnetization and anisotropy can be complicated. 13 Metal-bonded Co-ferrite composites are even more complex systems due to the metal additives and different processing from pure Co ferrite. 20 The temperature dependence can be explained by the changes of magnetostriction, anisotropy, spontaneous magnetization and pinning of domain walls caused by the availability of increased thermal energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to control the magnetostrictive properties has resulted in several studies including the influence of vacuum sintering, 1 annealing and quenching heat treatment, 2 metal bonding, 3 and cation substitutions. [4][5][6][7] Of these, cation substitution has been found very useful for improving the strain response of cobalt ferrite to applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Chemical substitution can enhance the properties of cobalt ferrite by altering the cation distribution in the cubic spinel structure, therefore, influencing the magnetoelastic properties of these materials. Previous studies have shown that the substitution of M 3+ ͑Mn 3+ , Cr 3+ , and Ga 3+ ͒ 2,3,7 in place of some of Fe 3+ reduces the hysteresis and increases the strain derivative of cobalt ferrite for certain compositions with, however, a decline or no improvement in the magnitude of magnetostrictive strain amplitude.…”
Section: Introductionmentioning
confidence: 99%